Accessibility Study For Persons With Disabilities In Tourism Destinations: A Case Study In The Malioboro Area, Yogyakarta - Mahmudah Budiatiningsih; Siti Hamdiah Rojabi (Faculty of Economics and Business, University of Mataram, 2023)
The Malioboro area is an icon of Yogyakarta tourism as well as a cultural heritage and an economic center which makes it always crowded with visitors. The large number of uncontrolled space users makes Malioboro often reported as an inaccessible area for tourists, especially people with disabilities. Even though according to Tourism Act of Indonesia No. 10 2009 states that tourists with special needs have the right to receive services according to their needs. Therefore, research related to accessibility for persons with disabilities in the Malioboro area is needed to find out the fulfilment of the rights of tourists with special needs in the area. The research method used is descriptive qualitative. Data collection techniques were carried out by means of literature studies, observation and documentation. While data analysis was carried out by comparing the facts found in the field with the theory of accessibility of the urban environment and cultural heritage. The results of the study show that accessibility indicators in the form of parking areas, vertical movement, public hygiene facilities and prices are available. While the indicators for communication, signage and horizontal movement facilities have not met the indicators. Based on these findings, the Malioboro area is accessible for general tourists but not yet fully accessible for persons with disabilities.